UNRAVELING THE CONTRIBUTIONS OF LEONARD BLOOMFIELD TO LINGUISTICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the enduring contributions of Leonard Bloomfield to the field of linguistics. It highlights his pioneering work in structural linguistics, descriptive analysis, and the study of phonology, morphology, and syntax. Through an examination of Bloomfield’s influential theories and methodologies, we gain insights into his lasting impact on the field of linguistics.